Microtexture analysis of copper‐doped iron oxide thin films prepared by air pneumatic spray. (14th June 2022) - Ghribi, Faouzi; Ţălu, Ştefan; Chouikh, Fethi; Bouznit, Yazid; Boudour, Samah; Méndez‐Albores, Alia; Cordova, Gabriel Trejo
Abstract: The stereometric and fractal concepts are crucial tools to analyse, to verify, to report 3‐D microtexture of thin film surfaces on the nanometre scale and thereby to generate useful topographic characteristics for better understanding and steering them toward further improvements and rational use in modern applications. At first, the present work aimed to prepare hematite α‐Fe2 O3 thin films with (0, 2, 4, 6 and 8 wt%) of Cu doping by using the air pneumatic spray method. Subsequently, the obtained pure α‐Fe2 O3 and Cu‐doped α‐Fe2 O3 thin films were characterised by XRD device, which determines their polycrystalline nature with the rhombohedral hematite structure. Analysis by UV‐VIS absorption showed that the transmittance of the thin films is extinct in the wavelength from approximately 500 to 800 nm, revealing that the films have good optical absorbance in the visible region. The obtained bandgap values varied between 2.23 and 2.21 eV. At second stage, the stereometric and fractal analysis are applied on 3‐D image data of pure α‐ Fe2 O3 and Cu‐doped α‐Fe2 O3 thin films, which in prior generated using AFM device. Accordingly, the obtained statistical parameters such as surface roughness, density distribution of peaks, depths etc. were used to understand the influence of Cu doping on the 3D microtexture of pure α‐ Fe2 O3 and Cu‐doped α‐ Fe2 O3 thin film surfaces. Lay description: In this study, the characterisation of copper‐doped iron oxide thin films prepared by air pneumatic spray was made by the crystal structure, optical properties and atomic force microscopy (AFM) measurements. Based on AFM micrographs the 3‐D surface microtexture of thin films was assessed by (a) the peak count and depth histograms; (b) the surface texture directions using polar graphs (isotropy; first direction; second direction; and third direction); (c) the contour lines, photo simulation and parameters of furrows (maximum depth of furrows; mean depth of furrows and mean density of furrows); (d) the fractal dimensions; (e) the height parameters: root mean square height, skewness, kurtosis, maximum peak height, maximum pit height, maximum height and arithmetic mean height. The obtained results demonstrated the possibility of the growth of high‐quality Cu‐doped α‐Fe2 O3 thin films with special topographic properties.